Higher or Lower Hemoglobin Transfusion Thresholds for Preterm Infants. Issue 2 (24th June 2021) - Kirpalani, H.; Bell, E.F.; Hintz, S.F.; Tan, S.; Schmidt, B.; Chaudhary, A.S.; Johnson, K.J.; Crawford, M.M.; Newman, J.E.; Vohr, B.R.; Carlo, W.A.; D'Angio, C.T.; et al.
Abstract : ( N Engl J Med . 2020;383:2639–2651) Extremely-low birthweight infants are commonly treated with packed red-cell transfusions to treat low hemoglobin, but transfusion protocols vary. Randomized control trial (RCT) evidence is limited, and more evidence is needed to evaluate low and high hemoglobin thresholds in terms of complications. This study, informed by a previous study of more than 450 neonates, compared transfusions at low and high hemoglobin thresholds in terms of incidence of death or neurodevelopmental impairment in infants at 22 to 26 months of age.